2020
DOI: 10.1161/circ.142.suppl_3.16742
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 16742: Single-Cell Transcriptional and Epigenomic Dissection of Human Heart in Health and Coronary Artery Disease Reveals Cell-type-Specific Driver Genes and Pathways

Abstract: Genome-wide association studies have uncovered over 200 genetic loci underlying coronary artery disease (CAD), providing great hope for a deeper understanding of the causal mechanisms leading to this disease. However, in order to understand CAD at the molecular level, it is necessary to uncover cell-type-specific circuits and to use these circuits to dissect driver variants, genes, pathways, and cell types, in normal and diseased tissues. Here, we provide the most detailed single-cell dissection of human heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, clinical trials showed benefit for Canakinumab in heart failure, suggesting a causal role for IL-1β in its pathogenesis 106 . Although recent studies pointed to cytokine-mediated fibroblast activation 107 and expansion of stressed CMs in ischemia 108 , the precise cellular mechanisms responsible for fibroblast activation or CM transition to a stressed status remains unclear. Our finding of inflammatory cytokine receptor expression in the vCM3_stressed cells provides a potential mechanism mediating CM susceptibility to inflammation, remodelling, and death.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, clinical trials showed benefit for Canakinumab in heart failure, suggesting a causal role for IL-1β in its pathogenesis 106 . Although recent studies pointed to cytokine-mediated fibroblast activation 107 and expansion of stressed CMs in ischemia 108 , the precise cellular mechanisms responsible for fibroblast activation or CM transition to a stressed status remains unclear. Our finding of inflammatory cytokine receptor expression in the vCM3_stressed cells provides a potential mechanism mediating CM susceptibility to inflammation, remodelling, and death.…”
Section: Discussionmentioning
confidence: 99%